From: Sam Takoy on
Hi,


I have a situation where I have to simplify an expression that contains
x and h, but x is given implicitly by h, so I can't explicitly eliminate
it. So here's a simpler example that I'm trying and it does nothing:

Assuming[x^2 + x == h, (x^2 + x)^2+h] // FullSimplify

Is there a way to make this work?

Thanks!

From: Bob Hanlon on

Use the assumption directly in Simplify or FullSimplify

Simplify[(x^2 + x)^2 + h, x^2 + x == h]

h (h+1)

FullSimplify[(x^2 + x)^2 + h, x^2 + x == h]

h (h+1)

Or put Simplify or FullSimplify within the scope of the Assuming construct

Assuming[x^2 + x == h, Simplify[(x^2 + x)^2 + h]]

h (h+1)

Assuming[x^2 + x == h, FullSimplify[(x^2 + x)^2 + h]]

h (h+1)


Bob Hanlon

---- Sam Takoy <sam.takoy(a)yahoo.com> wrote:

=============
Hi,


I have a situation where I have to simplify an expression that contains
x and h, but x is given implicitly by h, so I can't explicitly eliminate
it. So here's a simpler example that I'm trying and it does nothing:

Assuming[x^2 + x == h, (x^2 + x)^2+h] // FullSimplify

Is there a way to make this work?

Thanks!


--

Bob Hanlon


From: Sam Takoy on
Thanks for all this response and all that haven't showed up on the
newsgroup yet.

Here's my actual problem:

Assuming[ a Cosh[H/(2 a)] == 1,
FullSimplify[
Cosh[H/a] +
1/2 ((H/a - H/a Cosh[H/a] + 2 Sinh[H/a]) Sinh[H/(2 a)] )/(
H/(2 a) Sinh[H/(2 a)] - 1/a)]]

and the answer is "1";

My version of Mathematica (7) fails to do this simplification.

Thanks again!





On 7/20/2010 7:55 AM, Bob Hanlon wrote:
> Use the assumption directly in Simplify or FullSimplify
>
> Simplify[(x^2 + x)^2 + h, x^2 + x == h]
>
> h (h+1)
>
> FullSimplify[(x^2 + x)^2 + h, x^2 + x == h]
>
> h (h+1)
>
> Or put Simplify or FullSimplify within the scope of the Assuming construct
>
> Assuming[x^2 + x == h, Simplify[(x^2 + x)^2 + h]]
>
> h (h+1)
>
> Assuming[x^2 + x == h, FullSimplify[(x^2 + x)^2 + h]]
>
> h (h+1)
>
>
> Bob Hanlon
>
> ---- Sam Takoy<sam.takoy(a)yahoo.com> wrote:
>
> =============
> Hi,
>
>
> I have a situation where I have to simplify an expression that contains
> x and h, but x is given implicitly by h, so I can't explicitly eliminate
> it. So here's a simpler example that I'm trying and it does nothing:
>
> Assuming[x^2 + x == h, (x^2 + x)^2+h] // FullSimplify
>
> Is there a way to make this work?
>
> Thanks!
>
>
> --
>
> Bob Hanlon
>
>


From: Murray Eisenberg on
Try:

Assuming[x^2 + x == h, Simplify[(x^2 + x)^2 + h]]

Your original expression means the same thing as:

FullSimplify[ Assuming[x^2 + x == h, (x^2 + x)^2+h] ]

And that's clearly not what you intend, which is:

Assuming[[x^2 + x == h, FullSimplify[(x^2 + x)^2 + h] ]

Actually, Simplify will do nicely instead of FullSimplify here.

On 7/20/2010 3:43 AM, Sam Takoy wrote:
> Hi,
>
>
> I have a situation where I have to simplify an expression that contains
> x and h, but x is given implicitly by h, so I can't explicitly eliminate
> it. So here's a simpler example that I'm trying and it does nothing:
>
> Assuming[x^2 + x == h, (x^2 + x)^2+h] // FullSimplify
>
> Is there a way to make this work?
>
> Thanks!
>

--
Murray Eisenberg murray(a)math.umass.edu
Mathematics & Statistics Dept.
Lederle Graduate Research Tower phone 413 549-1020 (H)
University of Massachusetts 413 545-2859 (W)
710 North Pleasant Street fax 413 545-1801
Amherst, MA 01003-9305